An android application for the USDA structural design software - Kannikanti, Rajesh (Kansas State University, 2013)
People are more inclined to use tablets instead of other computing devices due to their portability and ease of use. A number of desktop applications are now becoming available as tablet applications, with increasing demand in the market. Android is one of the largest and most popular open source platforms that offer developers complete access to framework APIs in order to develop innovative tablet applications. The objective of this project is to develop an Android application for the U.S. Department of Agriculture (USDA) Structural Design Software. The GUI for this software is developed to run on tablet devices powered by Android platform. The main features provided by the User Interface include: • Allowing the input to be saved in ASCII text format and displaying the simulation results in PDF format • Allowing the user to select the type of project or view help contents for the projects • Allowing the user to build the simulation for the selected type of project • Allowing the user to send the simulation results to an e-mail The backend for this software is supposed to replace the old FORTRAN source files with Java source files. FORTRAN to Java translation is performed using the FORTRAN to Java (F2J) translator. F2J is intended to translate old FORTRAN math libraries, but was not completely successful in translating these FORTRAN programs. To accomplish successful translation, some features (such as Common Blocks, IO operations) were removed from the FORTRAN source files before translation. After successful translation, the removed features were added again to the translated Java source files. The simulation results provided by the software are useful to design engineers to develop new structural designs.
Keywords: Hydraulic structural design software; FORTRAN to Java translation; Computer Science (0984)